2008
DOI: 10.1051/forest:2008069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and genetic relationships among most common identified morphotypes of critically endangered rare Moroccan species Argania spinosa (Sapotaceae) using RAPD and SSR markers

Abstract: . Molecular characterization and genetic relationships among most common identified morphotypes of critically endangered rare Moroccan species Argania spinosa (Sapotaceae) using RAPD and SSR markers. Annals of Forest Science, Springer Verlag/EDP Sciences, 2008, 65 (8), pp.1. Ann. For. Sci. 65 (2008) Abstract• The objective of this work is the molecular characterization of most common identified morphotypes of critically endangered rare Moroccan species Argania spinosa.• Eighteen RAPD markers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
0
21
1
1
Order By: Relevance
“…The authors' results showed that the genetic diversity of argan tree is relatively higher (PB% = 98.8% and H = 0.172) contrary to what has been reported by other studies on the same species (allozymes analysis [18] and RAPD [15,19]…”
Section: Genetic Diversitycontrasting
confidence: 55%
See 1 more Smart Citation
“…The authors' results showed that the genetic diversity of argan tree is relatively higher (PB% = 98.8% and H = 0.172) contrary to what has been reported by other studies on the same species (allozymes analysis [18] and RAPD [15,19]…”
Section: Genetic Diversitycontrasting
confidence: 55%
“…Although the genetic diversity of argan tree has been studied using agro-morphological [13][14][15][16] and biochemical markers [17,18], only few studies used molecular markers. Thus, Bani-Aameur and Benlahbil [15] used random amplified polymorphic DNA (RAPD) markers, Majourhat et al [19] utilized simple sequence repeats (SSR) markers to characterize the most common morphotypes and El-Mousadik and Petit [17] identified the haplotypes of this endangered species using PCR-restriction fragment length polymorphism (RFLP) of chloroplast DNA.…”
mentioning
confidence: 99%
“…To date, most of A. spinosa L. studies have been mainly focused on its fruit and oil (Alaoui et al, 1998;Bani-Aameur et al, 1999;Charrouf and Guillaume, 1999;Charrouf et al, 2002;Sparg et al, 2004;Harhar et al, 2014). However, there are few investigations that show basic information regarding the genetic variation within/among populations A. spinosa L. (El Mousadik and Petit, 1996;Majourhat et al, 2008), and AFLP markers have, to the best of our knowledge, never been used to analyze the genetic diversity of A. spinosa L.…”
Section: Introductionmentioning
confidence: 99%
“…This slight variation may be caused by primer detection mechanisms: 1) the loci detected by RAPD and ISSR were different; for RAPD, the inverted repeats and internal site were amplified, whereas ISSR amplified inter-segment repeats, and 2) RAPD primers used random sequences of 10 bases, and ISSR primers were based on anchored primer repeats of 15-24 bases; therefore, polymorphism would be different, and the number of polymorphic fragments would increase with the increased number of primers and could also cause the change in genetic distance. Classification results were different by using different technology, as has been published in several studies (Messaoud et al, 2007;Majourhat et al, 2008).…”
Section: Evaluation Of Genetic Similaritymentioning
confidence: 99%